2016
DOI: 10.1002/jrs.5052
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman and SER spectroscopy to unfold Lefranc's early organic pigment formulations

Abstract: The introduction of synthetic dyes and pigments into commerce in the late 19th century was a stimulating time for experimental scientists in their laboratory formulations and for artists in their usage. Nowadays, the period of pioneering syntheses and employment of synthetic organic colouring materials is highly intriguing for scientific research and for conservation purposes in heritage science. In this work, a combination of spectroscopic and chromatographic methods has permitted the elucidation of the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Mixing eosin (Pigment Red 90) and phloxine B (Acid Red 92) is mentioned in the historical treatise The Dyeing of Paper Pulp by Julius Erfurt, a practical manual, dated 1901, for use by papermakers, paper stainers, students and others, and phloxine B was detected by FT-Raman in one of the samples of actual dyed papers included in the book to illustrate each recipe [27]. In this case, it can be hypothesised that phloxine B was present in the powder as its aluminium lake, known as Pigment Red 174.…”
Section: Xanthene Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixing eosin (Pigment Red 90) and phloxine B (Acid Red 92) is mentioned in the historical treatise The Dyeing of Paper Pulp by Julius Erfurt, a practical manual, dated 1901, for use by papermakers, paper stainers, students and others, and phloxine B was detected by FT-Raman in one of the samples of actual dyed papers included in the book to illustrate each recipe [27]. In this case, it can be hypothesised that phloxine B was present in the powder as its aluminium lake, known as Pigment Red 174.…”
Section: Xanthene Pigmentsmentioning
confidence: 99%
“…Due to the poor solubility of organic lake pigments and synthetic pigments in any medium (including water or organic solvents), the most commonly used approaches for their detection and characterisation exploit Raman spectroscopy or, whenever possible, surface-enhanced Raman spectroscopy (SERS) [18][19][20][21][22][23][24][25][26][27][28], thanks to the availability of dedicated spectral libraries. Whenever sampling has been permitted, analytical pyrolysis coupled with gas chromatography-mass spectrometry (Py-GC/MS) [1,[29][30][31][32] has been successfully applied.…”
Section: Introductionmentioning
confidence: 99%
“…Gabrieli and co‐workers used micro‐Raman and SERS to unfold Lefranc's early organic pigment formulations. In this work, a combination of spectroscopic and chromatographic methods permitted the elucidation of the chemical composition of 16 early synthetic organic pigment powders from the Lefranc experimental laboratory collection dating between 1890 and 1914 . Gao et al demonstrated the on‐site detection of phosgene agents by SERS coupled with a chemical transformation approach.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…The elucidation of the chemical composition of 16 early synthetic organic pigment powders from the Lefranc experimental laboratory collection dating 1890–1914 was performed by Gabrieli et al . It can be hypothesized that the most successful of these formulations could have been finalized in paint tubes and released onto the market, meaning that they may even be found in artworks from the same period.…”
Section: Raman Spectroscopy Of Organic‐based Materialsmentioning
confidence: 99%